(untitled) (Fiep Bulletin - online, 2013)
Brazilian immaterial cultural patrimony, the capoeira brings with her synonyms of resistance, struggle, vagrancy and camaraderie. In this context, we have as protagonists, figures that incorporate their practice in such a way, that their life stories become very similar to the capoeira herself. These true social actors have had different process of formation during the years, its on the nuances of this process that are established the questions that lead this work. Which are the differences in the formation process of the masters in the history of capoeira? Which is the importance of these masters before their pares? Processes that distinguish themselves mostly by the first decades of the XX century, moment in what emerge two of the most important and recognized Masters in the history of capoeira: Master Bimba and Master Pastinha, from which, was described a little about their life’s trajectory. The describing character, supported by oral elements and bibliographic revision, this the article here aims to a problematic about the formation of the Master differing it by the styles Angola and Regional.